2006
DOI: 10.3233/jad-2006-9409
|View full text |Cite
|
Sign up to set email alerts
|

Thoughts on B-vitamins and dementia

Abstract: The B-vitamins, including vitamins B12, B6, B1, B2, niacin (B3) and folate (B9), have been implicated as protective risk factors against cognitive decline and Alzheimer's disease. This commentary reviews the evidence to support protective relations of these vitamins, including consideration of known vitamin deficiency syndromes, theories of underlying biologic mechanisms, and the epidemiologic evidence. We also comment on the potential benefits and harms of vitamin supplementation as well as make recommendatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 48 publications
0
54
1
2
Order By: Relevance
“…Some studies have shown that higher intakes of vitamin B 12 and folate are related to better cognitive functioning or lower AD risk in the elderly,35–41 possibly due to their ability to reduce homocysteine levels, although results are not conclusive 41. β-Carotene (a major precursor to vitamin A) might have beneficial effects via its antioxidant or Aβ antioligomerisation effects 42–47.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that higher intakes of vitamin B 12 and folate are related to better cognitive functioning or lower AD risk in the elderly,35–41 possibly due to their ability to reduce homocysteine levels, although results are not conclusive 41. β-Carotene (a major precursor to vitamin A) might have beneficial effects via its antioxidant or Aβ antioligomerisation effects 42–47.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, we observed positive associations between folate and brain glucose metabolism in an NL, albeit at risk population, although folate levels were generally moderate. The literature indicates that whereas higher food intake of folate may be beneficial, high intake levels of folic acid (the synthetic form of folate) may be harmful, particularly in individuals with low vitamin B 12 status,41 as high dosages of folic acid may mask vitamin B 12 deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Several comprehensive reviews and meta-analyses discussing the impact of B vitamins on cognition have been published and generally point to null or inconclusive results. 4,2228 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are a limited number of prospective cohort studies on B vitamins and dementia, and the findings have not been consistent. Very few prospective studies examined the levels of B vitamins and Hcy in relation to incidence of dementia (Luchsinger et al, 2004;Corrada et al, 2005;Ravaglia et al, 2005;Morris et al, 2006b;Luchsinger et al, 2007b;Wald et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamins B complex (especially, folate, vitamins B 12 and B 6 ) has been given much attention as preventive factors against cognitive decline and dementia (Kuo et al, 2005;Morris et al, 2006b;Schneider et al, 2006;Reynolds, 2006;Sachdev, 2005;Troen and Rosenberg, 2005;Luchsinger et al, 2007a). The primary theoretical basis *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%